2022
DOI: 10.15586/aei.v50i5.592
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of serum IL-12, IL-16, and IL-17A as diagnostic biomarkers in children with cow’s milk protein allergy

Abstract: Background: Cow’s milk protein allergy (CMPA) is an abnormal immune response caused by milk proteins and is most common in infancy and early childhood. Statistics revealed up to 7.5% of children suffered from milk allergy. Its clinical symptoms were characterized by diversity, non-specificity, and can affect multiple systems, including the digestive tract, skin, and respiratory tract. In this study, we aimed to investigate the effects of IL-12, IL-16, and IL-17A on diagnosing and monitoring CMPA in children fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Since an adverse immunological reaction to egg proteins causes atopic dermatitis and eosinophilic esophagitis, it follows that egg allergy is an IgE antibody-mediated allergy [ 225 , 226 ]. Egg proteins’ ability to provoke an immune response is reflected in their stability in the face of heat and enzymatic digestion [ 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 ]. While both egg components contain proteins that can trigger an allergic reaction, the allergenic potential of EW proteins is greater than that of EY proteins.…”
Section: Allergenicity From Egg Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since an adverse immunological reaction to egg proteins causes atopic dermatitis and eosinophilic esophagitis, it follows that egg allergy is an IgE antibody-mediated allergy [ 225 , 226 ]. Egg proteins’ ability to provoke an immune response is reflected in their stability in the face of heat and enzymatic digestion [ 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 ]. While both egg components contain proteins that can trigger an allergic reaction, the allergenic potential of EW proteins is greater than that of EY proteins.…”
Section: Allergenicity From Egg Proteinsmentioning
confidence: 99%
“…In conclusion, these studies suggest that hydrolyzed egg proteins may positively impact weight management, appetite regulation, and metabolic health. However, further research is required to fully comprehend the underlying mechanisms behind these effects and determine the optimal dosages and long-term safety of hydrolyzed egg proteins [ 78 , 227 , 301 , 306 ]. Remembering that protein intake should be balanced with other dietary factors, such as fiber and healthy fats, for optimal weight management and overall health.…”
Section: Bioactive Peptides Derived From Egg Proteinmentioning
confidence: 99%
“…Cytokines play a significant role in viral infection by regulating cell signaling pathways. It has been shown that cytokines can be involved directly in disease pathogenesis [ 50 ]. Viruses led to the induction of cytokine genes, which can help viral genome replication.…”
Section: A Brief Description Of the Role Of The Il-2 Family In Viral ...mentioning
confidence: 99%
“…Although elevated levels of IL-16 have been found in very heterogeneous clinical settings, the study of the involvement of IL-16 in pathophysiological processes is rather incomplete. Thus, high concentrations of IL-16 have been detected in the blood of infants who developed cow's milk protein allergy (Mao et al 2022), atopic dermatitis (Zheng et al 2016), systemic sclerosis (Kawabata et al 2020), chronic lymphocytic leukemia (Wu et al 2023) and in the urine of patients with lupus nephritis (Häyry et al 2022). Related to the central nervous system, IL-16 is expressed in immune cells or resident microglia and astrocytes during multiple sclerosis (Skundric et al 2015;Hridi et al 2021).…”
Section: Introductionmentioning
confidence: 99%